2018
DOI: 10.1371/journal.pone.0189932
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of delayed graft function and long-term graft survival by serum and urinary neutrophil gelatinase–associated lipocalin during the early postoperative phase after kidney transplantation

Abstract: Neutrophil gelatinase-associated lipocalin (NGAL) has emerged as an early marker protein for kidney dysfunction in various clinical settings. In this prospective study we evaluated serial changes of serum and urinary NGAL within the first 7 days after kidney transplantation in 170 consecutive recipients. The main focus of this study was to assess the performance of serum and urinary NGAL in the prediction of delayed graft function (DGF) and two-year graft and patient survival. Serum and urine samples of 170 pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…Furthermore, the ability of creatinine to detect functional impairment is less than 50% (21). Several studies have been evaluated the role of urine or serum NGAL in predicting DGF after kidney transplantation, compare with traditional biomarkers such as serum Cr and urine output (22)(23)(24). Similar to our study they showed that NGAL level was more useful than serum Cr in early predicting DGF.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Furthermore, the ability of creatinine to detect functional impairment is less than 50% (21). Several studies have been evaluated the role of urine or serum NGAL in predicting DGF after kidney transplantation, compare with traditional biomarkers such as serum Cr and urine output (22)(23)(24). Similar to our study they showed that NGAL level was more useful than serum Cr in early predicting DGF.…”
Section: Discussionsupporting
confidence: 83%
“…Plasma and urine NGAL were evaluated and compare in some studies to investigate their performance to predict DGF (21,22,30). In some studies plasma NGAL showed an obviously higher sensitivity and a slightly higher speci city than those of urine NGAL, which supported the superiority of plasma NGAL over urine NGAL in predicting DGF within 24 hours following kidney transplantation (30).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Increased release from ischemia-injured tubular cells has been proved to discriminate patients at risk for AKI. Blood NGAL (bNGAL)—performed on serum/plasma—and urine NGAL (uNGAL) were shown to predict DGF in the early post-operative period, whereas its meaning as a perfusion fluid biomarker has already been discussed [ 15 , 21 ].…”
Section: Iri and Dgfmentioning
confidence: 99%
“…In a 3-year DCD kidney registry analysis, Lim et al [24] reported that the recipients of DCD kidneys with DGF experienced a higher incidence of acute rejection and overall graft loss. Gill et al [25] observed that the DGF-associated risk of graft failure was greatest in the rst post-transplant year. A meta-analysis by Yarlagadda et al veri ed the association between DGF, acute rejection, and graft survival.…”
Section: Discussionmentioning
confidence: 99%